2019
DOI: 10.1099/acmi.0.000026
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase gene polymorphisms of Staphylococcus aureus isolates from patients at Kosti Teaching Hospital, Sudan

Abstract: Background Staphylococcus aureus is a common cause of nosocomial infections. Epidemiological typing of S. aureus enables control of its spread. The objective of this study was to investigate coagulase gene polymorphisms of S. aureus isolated from patients at Kosti Hospital in Sudan. Methods In total, 110 S. aureus isolates were recovered from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Similarly, Afrogh et al [27] reported six different patterns of coa gene among S. aureus strains isolated from staff nose and patients in Iran. However, other similar results were achieved by Younis Omar et al [28] and Ibrahim et al [29]. In contrast, a study performed by Abdulghany et al [30] distinguished 15 different coa types among 58 MRSA isolates.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, Afrogh et al [27] reported six different patterns of coa gene among S. aureus strains isolated from staff nose and patients in Iran. However, other similar results were achieved by Younis Omar et al [28] and Ibrahim et al [29]. In contrast, a study performed by Abdulghany et al [30] distinguished 15 different coa types among 58 MRSA isolates.…”
Section: Discussionsupporting
confidence: 59%
“…In an Egyptian study conducted by Abdulghani and Khairy on 58 MRSA strains recovered from clinical isolates, 15 diferent coa types with the prominence of coa type X (16.6%) were identifed [34]. In a Sudanese study conducted by Ibrahim et al, resistance to methicillin was found to be 56% and coa type III as the predominant type was reported (55.5%) [35].…”
Section: Discussionmentioning
confidence: 99%